Sundanese Cultural Creativity at Mutiara 2 High School, Bandung City - Imas Nur Asiah; Metusael Dera Saputra Marchasan; Yusup; Rima Irmayanti (Indonesian Journal of Contemporary Multidisciplinary Research, 2023)
This journal reviews Sundanese cultural creativity at Mutiara 2 High School, Bandung City. This study aims to determine the creativity of Sundanese culture at Mutiara 2 High School, Bandung City. This type of research is participant qualitative research through interviews with informants and group discussions. Creativity is a person's ability to give birth to something new, both in the form of ideas and real work, which is relatively different from what has existed before. In developing Sundanese cultural creativity at Mutiara 2 High School in Bandung City, apart from holding a traditional ceremony for the release of class XII students, they also held Thursday Nyunda, where students wear Sundanese-based clothing, Hajat Cai Performances and Silat Tajimalela Shows. By referring to Sundanese cultural values, students can maintain and preserve Sundanese cultural creativity so that it is maintained